Seasonally persistent foraging niche segregation between sympatric Southern Rockhopper and Magellanic penguins breeding at Isla de los Estados, Argentina - Rosciano, Natalia Gimena; Polito, Michael J; Raya Rey, Andrea Nélida (Journal of Ornithology)
Variation in the foraging strategies used among species is a key factor in determining the trophic structure of ecological communities. Moreover, foraging niche differentiation could be driven by inter-specific competition and/or variation within species due to seasonal, age, sex and/or individual factors. Using stable isotope analysis, we assessed inter- and intra-specific differences in the foraging niches of female Southern Rockhopper penguin (Eudyptes chrysocome; SRP) and male and female Magellanic penguins (Spheniscus magellanicus; MP) at Isla de los Estados, Argentina. We sampled whole blood and feathers from breeding adults, representing the breeding and pre-moult periods over two consecutive years (2012 and 2013). We also compared stable isotope values between tissue to test for consistency in individuals foraging niches and the potential for foraging niche specialisation and segregation within breeding pairs. We observed clear foraging niche segregation between species that persisted during both breeding and pre-moult periods. SRP foraged in more oceanic/pelagic waters (lower δ13C values) while MP used coastal/benthic foraging habitats (higher δ13C values). In addition, SRP fed on lower trophic level prey (low δ15N values) relative to MP during both time periods. The isotopic foraging niches of MP highly overlapped between sexes at the population level and there was little to no evidence of niche segregation within breeding pairs or individual consistency in the seasonal foraging niche of both species. The results suggest that inter-specific foraging niche segregation is likely a more important factor influencing the trophic ecology and foraging behaviours of these species, relative to intra-specific factors. Even so, the persistence of inter-specific foraging niche segregation outside the breeding season suggests that either the potential for competition for food resource or foraging habitats remain high during this time or that the ultimate factors responsible for foraging niche segregation among ...